2004
DOI: 10.1002/ana.20151
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of motor cortical repetitive transcranial magnetic stimulation induces

Abstract: Repetitive transcranial magnetic stimulation (rTMS) recently has been assessed as a noninvasive treatment modality for movement and psychiatric disorders, whereas the mechanism underlying the therapeutic effects is not fully understood. Studies in rodents showed lasting functional changes in some selected regions, such as limbic-associated structures, but unfocused brain stimulation did not clarify the regional effects. To address the topographical and temporal profiles of the effects on glucose metabolism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 45 publications
(70 reference statements)
1
30
0
4
Order By: Relevance
“…Furthermore, these improvements were observed two weeks after the end of the rTMS protocol. Although the mechanism of this delay remains to be determined, possible cumulative effects of rTMS and a long-lasting effect of rTMS, which lasted up to 8 days in the primate brain [14], might partly explain this delay.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these improvements were observed two weeks after the end of the rTMS protocol. Although the mechanism of this delay remains to be determined, possible cumulative effects of rTMS and a long-lasting effect of rTMS, which lasted up to 8 days in the primate brain [14], might partly explain this delay.…”
Section: Discussionmentioning
confidence: 99%
“…10 The above-mentioned studies addressed short-term effects, while another study that assessed the long-term effects of rTMS in monkeys found that 5-Hz rTMS applied to the precentral gyrus reduces glucose metabolism in the motor and premotor cortices and increased metabolism in the cingulate and orbitofrontal cortices for a period lasting at least 8 days. 14 One recent study demonstrated decreased functional magnetic resonance imaging activation in pain networks including the secondary somatosensory cortex after 10-Hz rTMS of the primary motor cortex. 15 However, the effects of rTMS on local and global cortical reorganization and the precise underlying mechanisms are still unknown.…”
Section: Cortico-cortical Modulationmentioning
confidence: 99%
“…The prefrontal and cingulate cortices are known as association cortical areas integrating cortical functions of other areas, such as decision making and/or inhibitory control on motor pathways. 29,30 The temporal relationships of the rTMS effects have been assessed in the primate brain 14 by performing FDG-PET serially before, during, and up to 16 days after 5-Hz rTMS of the precentral gyrus. Glucose metabolism decreased in the motor and premotor cortices and increased in the limbic-associated areas such as the cingulate and orbitofrontal cortices, and those changes continued for at least 8 days, suggesting relatively long-lasting effects of rTMS in the functionally connected cortical areas.…”
mentioning
confidence: 99%
“…This strongly suggests that brain activity can be differently excited if patients are drug-na ï ve or when comparing off versus on medication, or off versus on DBS. Similarly, a cumulative effect should also be considered (Hayashi et al, 2004;Khedr et al, 2006). Some studies reported greater motor improvement as measured by the UPDRS-III after the fourth week of rTMS, but not before (Hamada et al, 2008).…”
Section: Imaging Tms Effects In Pdmentioning
confidence: 99%